Effectiveness of Problem-Based Learning Model in Science Learning: A Meta-Analysis Study - Abdul Rahman; Ilwandri Ilwandri; Tomi Apra Santosa; Revi Gina Gunawan; Yayat Suharyat; Ringgo Putra; Aulia Sofianora (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effect and impact of the overall research on the Problem-based learning model in science learning. This type of research is a meta-analysis. The data sources in this study are 17 national and international journals published from 2017-2022. The process of searching for data sources through Google Scholar, ScienceDirect, Wiley, ProQuest, and Eric Journal. Inclusion criteria are research on problem-based learning models with experimental or quasi-experimental methods and measurement of learning outcomes to evaluate Problem-Based Learning learning models. The results showed that the average effect size value of all studies (ES = 1.40) was very high. This finding explains that the Problem-Based Learning model provides a very high positive impact on science learning. In addition, the Problem-Based Learning learning model is effective to be applied to students' science learning at school. Effect measurement in this study is influenced by the level of education, year of publication, learning outcomes, and sample size. Overall, the Problem-Based Learning model is very useful in increasing students' potential in facing the 21st century.